Kinetics of reduction leaching of manganese dioxide ore with Phytolacca americana in sulfuric acid solution - Jianrong Xue; Hong Zhong; Shuai Wang; Changxin Li; Jinzhong Li; Fangfang Wu (Journal of Saudi Chemical Society, 2016)
The leaching kinetics of reductive leaching of manganese from manganese dioxide ores (MDO) in dilute sulfuric acid in the presence of Phytolacca americana powder (PAP) was investigated. The effects of stirring speed, leaching temperature and leaching time, particle size, weight ratio of PAP to MDO (CW) and sulfuric acid concentration (CH) on the leaching efficiency of manganese were studied. The leaching efficiency of manganese based on the shrinking core model was found to be controlled by diffusion through the ash/inert layer composed of the associated minerals. The apparent activation energy is 15.18 kJ mol−1. The experimental results indicate reaction order of 0.797 for CH and 1.25 for CW. The overall leaching efficiency equations for MDO dissolution reaction with PAP in dilute sulfuric acid were proposed by a semi-empirical model.